Conceptualizing connections: Energy demand, infrastructures and social practices. (August 2015) - Shove, Elizabeth; Watson, Matt; Spurling, Nicola
Problems of climate change present new challenges for social theory. In this article we focus on the task of understanding and analyzing car dependence, using this as a case through which to introduce and explore what we take to be central but underdeveloped questions about how infrastructures and complexes of social practice connect across space and time. In taking this approach we work with the proposition that forms of energy consumption, including those associated with automobility, are usefully understood as outcomes of interconnected patterns of social practices, including working, shopping, visiting friends and family, going to school, and so forth. We also acknowledge that social practices are partly constituted by, and always embedded in material arrangements. Linking these two features together, we suggest that forms of car dependence emerge through the intersection of infrastructural arrangements that are integral to the conduct of many practices at once. We consequently explore the significance of professional – and not only 'ordinary' – practices, especially those of planners and designers who are involved in reconfiguring infrastructures of different scales, and in the practice dynamics that follow.